S=16t^2
if t=3
So you would plug it in
16(3)^2
Then you multipy
16*3^2
=144
It is easier if you use a calculator just type in ti 30 calculator online that should help
Answer:
Step-by-step explanation:
f(x) = x^2 + 4x + 4
f(x + a) = (x + a)^2 + 4(x + a) + 4
f(x + a) = x^2 + 2ax + a^2 + 4x + 4a + 4 Now combine like terms and use the distributive property.
f(x + a) = x^2 + (2a + 4)x + a^2 + 4a + 4
We are told that f(x + a) = x^2 - 6x + 9
So that means that
2a + 4 = - 6 Subtract 4 from both sides.
2a = - 6 - 4
2a = - 10 Divide by 2
a = - 10/2
a = - 5.
But you are not finished. You have to check the last part.
a^2 + 4x + 4 = 9
(a + 2)^2 = 9
Take the square root of both sides
sqrt(a+ 2)^2 = +/- 3
a+2 = 3
a = 1.
Does this work or is it extraneous? It is extraneous because it will not work for 2(a) + 4 = - 6
You get 6 = - 6 which is not correct. But you did give the second best answer.
a + 2 = - 3
a = - 3 - 2
a = - 5 which agrees with your previous answer.
===========
This is an extremely hard or tricky or sneaky problem. It takes a lot of conniving to get the right answer and 1 is not a left field answer. It just does not happen to be correct.
Answer:
4 * 14 = 56
Step-by-step explanation:
56/2 = 28
28/2 = 14
14/2 = 7
7/7 = 1
56 = 2 * 2 * 2 * 7
56 = (2 * 2) * (2 * 7)
56 = 4 * 14
Answer:
C = 1.
Step-by-step explanation:
x^2 - 2x = (x - 1)^2 - 1 so:
x^2 - 2x + C = (x - 1)^2 - 1 + C
So to get a perfect square C must be 1 ( as -1 + 1 = 0):-
(x - 1)^2 - 1 + 1 = (x - 1)^2
Checking this:
x^2 - 2x + 1
= (x - 1)(x - 1) which is a perfect square./
Answer:
20.137
Step-by-step explanation: